Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1021/la400786a
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pickering Emulsifiers Based on pH-Responsive Poly(2-(diethylamino)ethyl methacrylate) Latexes

Abstract: Emulsion copolymerization of 2-(tert-butylamino)ethyl methacrylate in the presence of divinylbenzene (DVB) cross-linker and monomethoxy-capped poly(ethylene glycol) methacrylate (PEGMA) macromonomer at 70 °C afforded sterically-stabilized latexes at approximately 10% solids at pH 9. Dynamic light scattering (DLS) and scanning electron microscopy (SEM) confirmed that relatively narrow size distributions were obtained. SEM confirmed the formation of spherical particles in the absence of any DVB cross-linker usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
130
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(132 citation statements)
references
References 66 publications
2
130
0
Order By: Relevance
“…193 The particles were zwitterionic in nature because of the presence of oppositely charged DEAEMA and SMA. 17 Instead, when CO 2 was performed for the switching on process and N 2 for the switching off process, no significant reduction in the size of the particles was detected even after 10 cycles. Switching on and off cycles were performed at room temperature with relatively fast response to the triggers.…”
Section: Self-assembly Of Polymers Containing Deaemamentioning
confidence: 90%
See 2 more Smart Citations
“…193 The particles were zwitterionic in nature because of the presence of oppositely charged DEAEMA and SMA. 17 Instead, when CO 2 was performed for the switching on process and N 2 for the switching off process, no significant reduction in the size of the particles was detected even after 10 cycles. Switching on and off cycles were performed at room temperature with relatively fast response to the triggers.…”
Section: Self-assembly Of Polymers Containing Deaemamentioning
confidence: 90%
“…11 The initiator-derived endgroups on each polymer chain, bearing an imidazole moiety, were protonated by CO 2 and provided stabilization of the latex particles. 17,193 DEAEMA and DMAEMA are both prone to hydrolysis, specifically at high temperatures and high pH. Therefore, the total amount of charge available for particle stabilization was limited, with the result being the solid content could not be increased to more than B7%.…”
Section: Free Radical Polymerization (Frp)mentioning
confidence: 99%
See 1 more Smart Citation
“…This may be important if repeated pH cycling is required, as the otherwise problematic accumulation of background salt is minimized. [11] It is also shown that a pH switch can induce an irreversible vesicle-to-worm morphological transition. This work represents an important new paradigm for pH-induced morphological transitions exhibited by block copolymer nano-objects.…”
mentioning
confidence: 99%
“…The fabrication procedure involves first preparing a Pickering emulsion and then solidifying the emulsion continuous phase. Pickering emulsion is a solid particle-stabilized emulsion [26][27][28][29][30][31][32], where solid particles are nearly irreversibly adsorbed at liquid-liquid interfaces and act as a barrier against coalescence making the resulted emulsions extremely stable [33][34][35][36]. Thus, Pickering emulsion templates are stable enough to maintain the designed porous structures in the fabrication procedure.…”
Section: Introductionmentioning
confidence: 99%